Tyre contact surface for the fatigue design of orthotropic steel bridge decks. (15th May 2023) - Rodenburg, Jorrit D.; Maljaars, Johan; Hengeveld, Sjoerd T.; Vervuurt, Adri H.J.M.
Abstract: The fatigue life of orthotropic steel bridge decks in road bridges depends on the load effects exerted by heavy lorries. The contact surface of tyres is one of the important variables. Measurements described in the literature demonstrate that the actual tyre contact surfaces of today's traffic representative for Europe are shorter and slightly wider than the contact surface defined for the load model in the European standard for fatigue loads in bridges — EN 1991-2. This paper derives a new, realistic tyre contact surface to be used with the tyre loads in EN 1991-2, in such a way that the load effects for fatigue are realistically captured and that the required safety level is met. Highlights: Fatigue of orthotropic bridge decks depends on the lorry tyre contact surface. The contact surface in Eurocode's Fatigue Load Model 4 is too long and narrow. The width of the traction axle (tyre-to-tyre distance) in the load model is too large. The finite element method is used to calibrate the contact surface in the load model. Realistic tyre contacts are therein compared to a square contact with uniform stress.